Наближення голоморфних функцій середніми Тейлора-Абеля-Пуассона - Савчук, В.В. (Український математичний журнал, 2007)
Исследуются приближения голоморфных в единичном круге функций f средними Aρ,r(f) при ρ→1−. В терминах погрешности приближения этими средними приведена конструктивная характеристика классов голоморфных функций Hʳp Lipα. Решена задача о насыщении Aρ,r(f) в пространстве Гарди Hp. We investigate approximations of functions f holomorphic in the unit disk by means Aρ,r(f) for ρ→1−. In terms of an error of the approximation by these means, the constructive characteristic of classes of holomorphic functions Hʳp Lipα is given. The problem of the saturation of Aρ,r(f) in the Hardy space Hp is solved.